SOCIALLY RESPONSIBLE UNIVERSITY: PERSPECTIVES OF UNIVERSITY’S TOP MANAGEMENT LEADERS - Aida Suraya Md.Yunus; Norzaini Azman; Shukran Abdul Rahman (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract Carnegie Foundation for Advancement of  Teaching described UCE as the “collaboration between higher education institutions (HEIs) and their larger communities (local, regional or state, national, and global) for the mutually beneficial exchange of knowledge and resources in a context of partnership and reciprocity.”  Thus the term socially responsible university was proposed by Teichler (2017) which refers to the need for a university to be relevant to the society and that “the university has to pay attention as well that it serves the generally agreed function of generating, preserving and disseminating knowledge appropriately.”  However, this function is the least emphasized by the university community and in criteria for promotion.  This Article examines the nature of and the factors affecting universities’ engagement with their communities from the multiple perspectives of top management leaders of the university.  Specifically, the research sought to access views on UCE and explores cultural and institutional barriers to involvement, and levels of recognition, support, and reward for community engagement. The article highlights the two perspectives from the respondents; their beliefs of what is currently occurring in their universities and their views on what ought to be occurring. Abstrak Carnegie Foundation for Advancement of Teaching (Yayasan Carnegie untuk Kemajuan pengajaran) menggambarkan university-community engagement (UCE) sebagai "kolaborasi antara institusi pendidikan tinggi (HEIs) dan komunitas mereka yang lebih besar (lokal, regional atau negara, nasional, dan global) untuk pertukaran pengetahuan dan sumber daya yang saling menguntungkan dalam konteks kemitraan dan timbal balik.” Dengan demikian istilah universitas yang bertanggung jawab secara sosial diusulkan oleh Teichler (2017) yang mengacu pada perlunya sebuah universitas menjadi relevan dengan masyarakat dan bahwa “universitas harus memperhatikan dalam melayani fungsi yang disepakati bersama untuk menghasilkan, melestarikan dan menyebarkan pengetahuan dengan tepat.” Namun, fungsi ini paling tidak ditekankan oleh komunitas universitas dan dalam kriteria untuk promosi. Artikel ini mengkaji sifat dan faktor-faktor yang mempengaruhi keterlibatan universitas dengan komunitas mereka dari berbagai perspektif pimpinan manajemen puncak pada universitas. Secara khusus, penelitian ini berupaya untuk mengakses pandangan tentang UCE dan mengeksplorasi hambatan budaya dan kelembagaan untuk keterlibatan, dan tingkat pengakuan, dukungan, dan penghargaan untuk keterlibatan masyarakat. Artikel ini menyoroti dua perspektif dari responden; keyakinan mereka tentang apa yang sedang terjadi di universitas mereka dan pandangan mereka tentang apa yang seharusnya terjadi.How to Cite : Md.Yunus, A. S., Azman, N. Rahman, S. A. (2017). Socially Responsible University: Perspectives of University’s  Top Management Leaders. TARBIYA: Journal of Education in Muslim Society, 4(2), 128-147. doi:10.15408/tjems.v4i2.8008. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.8008